The prospect of migration, sticky wages, and educated unemployment - Oded Stark; C. Simon Fan (University of Bonn, Center for Development Research (ZEF), 2011)
An increase in the probability of work abroad, where the returns to schooling are higher than at home, induces more individuals in a developing country to acquire education, which leads to an increase in the supply of educated workers in the domestic labor market. Where there is a sticky wage-rate, the demand for labor at home will be constant. With a rising supply and constant demand, the rate of unemployment of educated workers in the domestic labor market will increase. Thus, the prospect of employment abroad causes involuntary educated unemployment at home. A government that is concerned about educated unemployment and might therefore be expected to encourage unemployed educated people to migrate will nevertheless, under certain conditions, elect to restrict the extent of the migration of educated individuals.
Keywords: E24; F22; J24; O15; 330; Bildungsinvestition; Facharbeiter; Lohnrigidität; Unterbeschäftigung; Arbeitslosigkeit; Auswanderung; Bildungsertrag; Erwartungstheorie; Theorie